Kinesiophobia Predicts Physical Function and Physical Activity Levels in Chronic Pain-Free Older Adults - Naugle, Kelly M.; Blythe, Corinthian; Naugle, Keith E.; Keith, NiCole; Riley, Zachary A. (Frontiers in Pain Research, 2022)
Advanced aging is associated with a general decline in physical function and physical activity. The current evidence suggests that pain-related fear of movement (i.e., kinesiophobia) is increased in the general older adult population and impacts physical activity levels in chronic pain patients. However, whether kinesiophobia could impact physical activity and function in relatively healthy, chronic pain-free older adults remains unclear. Thus, the purpose of this study was to examine whether fear of movement due to pain predicted self-reported and objective levels of physical function and physical activity in healthy older adults without chronic pain. Fifty-two older adults enrolled in this study. Participants completed the International Physical Activity Questionnaire (IPAQ) and wore an accelerometer on the hip for 7 days to measure physical activity. Measures of sedentary time, light physical activity, and moderate to vigorous physical activity were obtained from the accelerometer. Measures of physical function included the Physical Functioning subscale of the Short Form-36, Short Physical Performance Battery (SPPB), the 30-s Chair Stand test, and a maximal isometric hand-grip. The Tampa Scale of Kinesiophobia (TSK) was used to measure fear of movement or re-injury associated with pain. Potential covariates included self-reported activity-related pain and demographics. Hierarchical linear regressions were conducted to determine the relationship of kinesiophobia with levels of physical activity and physical function, while controlling for activity related pain and demographics. TSK scores did not predict self-reported physical activity on the IPAQ. However, TSK scores predicted self-reported physical function (Beta= -.291, p=.015), 30-s Chair Stand test scores (Beta= -.447, p=.001), measures from the SPPB (Gait speed time: Beta= .486, p<.001; Chair stand time: Beta=.423, p=.003), percentage of time spent in sedentary time (Beta= .420, p=.002) and light physical activity (Beta= -.350, p=.008), and moderate to vigorous physical activity (Beta= -.271, p=.044), even after controlling for significant covariates. These results suggest that greater pain-related fear of movement/re-injury is associated with lower levels of light and moderate to vigorous physical activity, greater sedentary behavior, and worse physical function in healthy, chronic pain-free older adults. These findings elucidate the potential negative impact of kinesiophobia in older adults who don’t report chronic pain.